GYMNASIUM CALORIE SPECTRUM FLEXIBILITY AND MOBILITY OPTIMIZATION DESIGN - Rahman, Rasyad Tanzilur; Solakhudin, Nur Muhammad; Pangyom, Wanudya; Arifin, Zaenal; Afriliani, Nita; Aziz Thohari, Afandi Nur (EINSTEIN (e-Journal), 2024)
This research aims to produce Spektrum Gymnasium which is used as a progress monitoring tool and digital track of sports training that is accurate in building muscle in an efficient time and partners can monitor each customer's muscle-building exercise movements so that the calories wasted can be known, thereby increasing customer satisfaction. The research method begins with discussions with accompanying lecturers and partners. Implementation of activities begins with designing devices, collecting tools and software, and creating outputs in the form of Summit Health tool applications and manuals for using tools and applications. Partner assistance was carried out 6 times. Monitoring and evaluation were conducted to determine developments in using Summit Health tools and the Spectrum Gymnasium application. The sustainability of the Summit Health tool and the Spectrum Gymnasium application as a solution to problems and a guidebook can help in developing tools and applications to calculate calories for consumers independently. The results achieved are in the form of progress reports, final reports, guidebooks, social media accounts, Summit Health tools and Spectrum Gymnasium applications, scientific articles, Summit Health books, IoT-based Spectrum Gymnasium applications, IPR applications and activity publications. Conclusion Spektrum Gymnasium accurately monitors the progress of exercise training in building muscle efficiently. The monitoring feature makes it easier for gym partners to track exercise movements and calories burned, increasing customer satisfaction and exercise results, as well as strengthening customer loyalty and supporting sustainable business growth.